Answer :

osikbro

Answer:

[tex]x=0, \dfrac{1}{2}, -\dfrac{1}{2}[/tex]

Step-by-step explanation:

[tex]4x^3-x=0 \\\\x(4x^2-1)=0 \\\\x(2x-1)(2x+1)=0 \\\\x=0, \dfrac{1}{2}, -\dfrac{1}{2}[/tex]

Hope this helps!

Answer:

x=0    x = 1/2        x = -1/2

Step-by-step explanation:

4x^3 - x=0

Factor out an x

x(4x^2 -1) =0

Factor inside the parentheses  ( difference of squares  a^2 -b^2 = (a-b)(a+b))

x (2x-1)(2x+1) =0

Using the zero product property

x=0  2x-1 =0   2x+1 =0

x =0 2x=1       2x = -1

x=0    x = 1/2        x = -1/2